Oriental Studies in the U.S.A. - İhsanoğlu, Ekmeleddin, 1943-; Frye, Richard N.; Naby, Eden (My University, 1991)
Konferansta: Richard N. Frye, ABD`deki şarkiyat etüdleri; Eden Naby ise Ortadoğu`nun laik ve dini kimliği hakkında ayrıntılı bilgi sunmaktadır.
Secular Versus Religious Identity in the Middle East
With: Secular Versus Religious Identity in the Middle East / Eden Naby.
WAV and MP3 formats were created from the original audio cassette along with the CD.
There is humming and intermittent gaps in the recording.
Keywords: Secular and religious identity-Middle East; Oriental studies-United Stades of America; Conferences